DEVELOPING ICT-BASED SUPPLEMENTARY READING MATERIALS FOR THE SEVENTH-GRADE STUDENTS AT MADRASAH TSANAWIYAH MAARIF KARANGASEM - Sahrullah Sahrullah; I Nyoman Adi Jaya Putra Putra; Ni Luh Putu Sri Adnyani (Journey: Journal of English Language and Pedagogy, 2023)
This study aims at developing ICT-based supplementary reading materials for the seventh-grade students at Madrasah Tsanawiyah Maarif Karangasem. Specifically, this study identified the students' needs, described the design of the ICT-based supplementary reading materials, and identified the content validity and the quality of the ICT-based supplementary reading materials. This study followed the ADDIE approach, which consists of five steps, analyze, design, develop, implement, and evaluate. This study involved 40 seventh-grade students, two content experts, and one media expert. The study data were collected using questionnaires, interviews, observation, and expert judgment sheets. The researchers analyzed the data through qualitative and quantitative analysis. This study found that the students need reading materials with colorful designs, exciting pictures, videos, and online quizzes that can be accessed online. The developed ICT-based supplementary reading materials were proven to have high content validity. Besides, this study also identified that the ICT-based supplementary reading materials have good quality.